Analysis of consumer motivation on purchase intention of Flimty Fiber: A study on Flimty Fiber consumers in West Kalimantan - Soe, Sinta Bella; Listiana, Erna; Afifah, Nur; Juniwati, Juniwati; Purmono, Bintoro Bagus (Journal of Management and Digital Business, 2025)
This study analyzes the factors influencing consumer purchase intention of “Flimty Fiber” health products in West Kalimantan. These factors include health consciousness, utilitarian value, and subjective norms, with attitude as a mediating variable. The approach is quantitative research and data collection using a questionnaire with 200 respondents who meet the criteria. The sampling technique used was purposive sampling, and data analysis was carried out using the Partial Least Square (PLS) method. This study identified that health consciousness and utilitarian value significantly influence purchase intention. Attitude also mediates the relationship between utilitarian value, subjective norms, and purchase intention. However, health consciousness has no significant influence on attitude or an indirect influence on purchase intention, while subjective norms do not directly influence purchase intention. This research provides new perspectives for manufacturers and marketers of health products to prioritize functional value and pay attention to social pressure or social influence in building positive consumer attitudes toward products.